Drilling Down on Geothermal Potential : An Assessment for Central America - World Bank (World Bank, Washington, DC, 2017)
Economic growth in Central America has increased rapidly over the past 20 years. Currently, the gross domestic product (GDP) per capita for the six Central American countries of Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua and Panama averages approximately US$3,600. However, economic disparity in the Latin American region is the highest in the world. Despite impressive growth, 20 million people or half of the population in Central America are classified as poor. This assessment of the geothermal potential module is the fourth in the series; it provides an analysis of the energy context in the region focusing on the technology and past experiences of geothermal resources. The study aims to identify the challenges associated with development of geothermal generation, including physical, financial, regulatory and institutional barriers, and it outlines some possible strategies to overcome them at the regional and country-specific level with a view to establish a basis for policy dialogue and to provide decision-makers a reference document with a regional outlook. Energy, particularly electricity, is critical for economic development. It is needed to power machinery that supports income-generating opportunities. Countries that have affordable and reliable energy can more easily attract both foreign and domestic capital. Central America's vulnerability to external shocks in the energy sector has increased over the last years. The region depends on foreign supply of fossil fuels (oil, coal). Since the share of thermal generation in power supply has increased significantly in the last decade, exceeding installed capacity for hydropower, the rise and volatility of oil prices has a dramatic effect today on the region's economy. Together with integration, it has become increasingly clear that the region must develop its local energy endowment, which has generated a strong interest in renewable energy sources and technologies, such as hydropower, geothermal, and wind. Given its potential in the region, geothermal energy has attracted the attention of policymakers and private investors as a resource to further develop and supplement hydroelectric generation (and to reduce dependency on thermal generation).